Implementation of Education Management Standard in The Guidance of Private Islamic High School - Herson Anwar (Jurnal Pendidikan Islam, 2018)
This study aimed to review the implementation of education management standard for the development of private Islamic high school. This is the case study in Gorontalo City (one of big city in Indonesia). This study investigates the process of program enforcement, such as the management of curriculum section and learning activities, students, teachers and staffs, facilities, monetary sections, culture and school environment, as well as public relation and partnership. Data were collected by observation, interview, and the documentation. The result showed that the standard implementation of education management under the guidance of private Islamic high school has been conducted even there are some management components, which are not yet well conducted as the standard. The challenges are the low interest of parents to enroll their children at madrasah, unrepresentative service, inefficient financial planning, government and foundation policy, free education program, public relation program concern more on an internal program, and also the lack of parents’ knowledge about Islamic high school. The potencies of Islamic high school such as religion curriculum, extracurricular program, and complete facilities should be optimized.